2004
DOI: 10.1111/j.0001-6349.2004.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Well‐being and sense of coherence during pregnancy

Abstract: Our study shows that the SOC scale measures the capacity to cope with the unforeseeable process that child-bearing still implies today. The SOC scale questionnaire and the HI can complement the midwife's subjective evaluation of the pregnant woman's need for psychosocial support during pregnancy. If this is correct, the SOC scale and the HI could be of great value in clinical work within maternal health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
39
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 19 publications
7
39
0
4
Order By: Relevance
“…Overviews conclude that the SOC questionnaire shows a relatively high predictability, both from a short-and long-term perspective [2,3]. In addition, other studies (not mentioned in the overviews) have identified SOC as a predictor of: quality of life and depression among caregivers [4], well-being during pregnancy [5], employees' adjustment to foreign assignments [6], recovery following orthopaedic surgery [7], symptoms of PTSD and depression after miscarriage [8], psychosocial adjustment in men after acute myocardial infarction [9], and mortality [10]. Finally, SOC was not found to be a predictor for depression among mass-evacuated adults from Kosovo [11].…”
Section: Introductionmentioning
confidence: 92%
“…Overviews conclude that the SOC questionnaire shows a relatively high predictability, both from a short-and long-term perspective [2,3]. In addition, other studies (not mentioned in the overviews) have identified SOC as a predictor of: quality of life and depression among caregivers [4], well-being during pregnancy [5], employees' adjustment to foreign assignments [6], recovery following orthopaedic surgery [7], symptoms of PTSD and depression after miscarriage [8], psychosocial adjustment in men after acute myocardial infarction [9], and mortality [10]. Finally, SOC was not found to be a predictor for depression among mass-evacuated adults from Kosovo [11].…”
Section: Introductionmentioning
confidence: 92%
“…Frequently, women report a generalized feeling of wellbeing during pregnancy once early physical symptoms, such as nausea and vomiting, have passed. However, some researchers highlighted the fact that anxiety and mood disorders may worsen, in a manner indirectly mediated by psychosocial stressors [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…These studies all demonstrated an association between low s-IgA levels and stress in peripartum women. In terms of SOC score, Sjöström et al [33] reported that a woman's degree of SOC was a strong predictor of psychological well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Several published studies focused on the ability to cope with stress, which affects health status as a stress reaction [33][34][35][36][37]. Sjöström et al [33] used the sense of coherence (SOC) scale as the stress coping ability indicator in a study involving 120 pregnant women in Stockholm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation